Spirituality and health: subject experience in undergraduate school of nursing - Naiane Dias Simões; Priscila Gomes Martins; Renata Ohana Pereira dos Santos; Fabiana Ribeiro Santana; Calíope Pilger (Universidade Federal de Santa Maria, 2018)
Aim: to present the activities and experiences of nursing students in the subject of Spirituality and Health. Method: it is an experience report that configures the experiences of students of the eighth period of the nursing course of the aforementioned discipline in the second semester of the years of 2014 and 2015. The pedagogical strategies used in the discipline were: expository-dialogic classes, group activities, films, guests of the psychology area, portfolio structure, experience reports, case studies using nursing diagnoses. The scenarios used were the classroom, health institutions of other cities, and the external community. Results: from the students' speeches, it was possible to observe how important and necessary this discipline is to the undergraduate school of nursing, as it stimulates in the student the ability to go beyond the observable and helps to understand the other needs for the patients and their family, who receive the care. Final Considerations: to assist the patient in their integrality involves the care of the spiritual and religious dimensions and represents for the nurse a rescue of humanized care.